2019
DOI: 10.3390/s19214765
|View full text |Cite
|
Sign up to set email alerts
|

Obliquely Deposited Titanium Nitride Nanorod Arrays as Surface-Enhanced Raman Scattering Substrates

Abstract: In this work, titanium nitride (TiN) nanorod arrays were prepared as surface-enhanced Raman scattering (SERS) substrates using glancing angle deposition (GLAD) in a magnetron sputtering system. The nitrogen flow rate was varied from RN2 = 1 to 3 sccm, yielding five TiN uniform thin films and five TiN nanorod arrays. The figure of merit (FOM) of each TiN uniform film was measured and compared with the SERS signal of each TiN nanorod array. Rhodamine 6G (R6G) was used as the analyte in SERS measurement. For an R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…700 nm were observed in the absorption spectrum (Figure 1B), indicating optical activity over a large fraction of the visible spectrum. Previous studies have reported similar absorption profiles for nanostructured TiN and attributed those to the distinct plasmonic activity of the material [1,15,28]. LSPRs of TiN created upon light illumination have been proposed to manifest as broad absorption features that are located at specific frequencies characteristic for the specific nanostructure geometry.…”
Section: Optical Characterizationmentioning
confidence: 80%
See 4 more Smart Citations
“…700 nm were observed in the absorption spectrum (Figure 1B), indicating optical activity over a large fraction of the visible spectrum. Previous studies have reported similar absorption profiles for nanostructured TiN and attributed those to the distinct plasmonic activity of the material [1,15,28]. LSPRs of TiN created upon light illumination have been proposed to manifest as broad absorption features that are located at specific frequencies characteristic for the specific nanostructure geometry.…”
Section: Optical Characterizationmentioning
confidence: 80%
“…nanostructured TiN and attributed those to the distinct plasmonic activity of the material [1,15,28]. LSPRs of TiN created upon light illumination have been proposed to manifest as broad absorption features that are located at specific frequencies characteristic for the specific nanostructure geometry.…”
Section: Optical Characterizationmentioning
confidence: 99%
See 3 more Smart Citations